Bandwidth renormalization due to the intersite Coulomb interaction. (20th August 2019) - in 't Veld, Yann; Schüler, Malte; Wehling, Tim O; Katsnelson, Mikhail I; van Loon, Erik G C P
Abstract: The theory of correlated electrons is currently moving beyond the paradigmatic Hubbard U, towards the investigation of intersite Coulomb interactions. Recent investigations have revealed that these interactions are relevant for the quantitative description of realistic materials. Physically, intersite interactions are responsible for two rather different effects: screening and bandwidth renormalization. We use a variational principle to disentangle the roles of these two processes and study how appropriate the recently proposed Fock treatment of intersite interactions is in correlated systems. The magnitude of this effect in graphene is calculated based on cRPA values of the intersite interaction. We also apply the variational principle to benzene and find effective parameters comparable to those obtained by ab initio density matrix downfolding.